Psychological Well-Being of Single Mothers in Kuanheun Village - Bil Onim Ridwan Neolaka; Dian L. Anakaka; R. Pasifikus C. Wijaya (Universitas Nusa Cendana, 2025)
This study explores the psychological well-being of single mothers in Kuanheum Village, Kupang Regency. As single mothers face both emotional and financial challenges, their psychological condition deserves further study. The research used a descriptive quantitative approach with 52 participants. Data were collected using the Psychological Well-Being Scale based on Ryff's six dimensions. Results show that most participants (61.5%) had a moderate level of psychological well-being, with personal growth as the most developed dimension and positive relations with others as the least. These findings underscore the need for community support to enhance the psychological well-being of single mothers, especially in rural settings.